Comparison of in vitro-specific blood tests with tuberculin skin test for diagnosis of latent tuberculosis before anti-TNF therapy. Issue 12 (24th April 2007) - Sellam, Jérémie; Hamdi, Haifa; Roy, Carine; Baron, Gabriel; Lemann, Marc; Puéchal, Xavier; Breban, Maxime; Berenbaum, Francis; Humbert, Marc; Weldingh, Karin; Salmon, Dominique; Ravaud, Philippe; et al.
Abstract : Introduction: Latent tuberculosis infection (LTBI) is detected with the tuberculin skin test (TST) before anti-TNF therapy. We aimed to investigate in vitro blood assays with TB-specific antigens (CFP-10, ESAT-6), in immune-mediated inflammatory diseases (IMID) for LTBI screening. Patients and methods: Sixty-eight IMID patients with (n = 35) or without (n = 33) LTBI according to clinico-radiographic findings or TST results (10 mm cutoff value) underwent cell proliferation assessed by thymidine incorporation and PKH-26 dilution assays, and IFNγ-release enzyme-linked immunosorbent spot (ELISPOT) assays with TB-specific antigens. Results: In vitro blood assays gave higher positive results in patients with LTBI than without (p<0.05), with some variations between tests. Among the 13 patients with LTBI diagnosed independently of TST results, 5 had a negative TST (38.5%) and only 2 a negative blood assays result (15.4%). The 5 LTBI patients with negative TST results all had positive blood assays results. Ten patients without LTBI but with intermediate TST results (6–10 mm) had no different result than patients with TST result ⩽5 mm (p>0.3) and lower results than those with LTBI (p<0.05) on CFP-10+ESAT-6 ELISPOT and CFP-10 proliferation assays. Conclusion: Anti-TB blood assays are beneficial for LTBI diagnosis in IMID. Compared with TST, they show a better sensitivity, as seen by positive results in 5 patients with certain LTBI and negative TST, and better specificity, as seen by negative results in most patients with intermediate TST as the only criteria of LTBI. In the absence of clinico-radiographic findings for LTBI, blood assays could replace TST for antibiotherapy decision before anti-TNF.